Loss of myeloid cell-specific SIRPα, but not CD47, attenuates inflammation and suppresses atherosclerosis. Issue 15 (23rd December 2021) - Singla, Bhupesh; Lin, Hui-Ping; Ahn, WonMo; Xu, Jiean; Ma, Qian; Sghayyer, Moses; Dong, Kunzhe; Cherian-Shaw, Mary; Zhou, Jiliang; Huo, Yuqing; White, Joseph; Csányi, Gábor
Abstract: Aims: Inhibitors of the anti-phagocytic CD47-SIRPα immune checkpoint are currently in clinical development for a variety of haematological and solid tumours. Application of immune checkpoint inhibitors to the cardiovascular field is limited by the lack of preclinical studies using genetic models of CD47 and SIRPα inhibition. In this study, we comprehensively analysed the effects of global and cell-specific SIRPα and CD47 deletion on atherosclerosis development. Methods and results: Here, we show that both SIRPα and CD47 expression are increased in human atherosclerotic arteries and primarily co-localize to CD68 + areas in the plaque region. Hypercholesterolaemic mice homozygous for a Sirpa mutant lacking the signalling cytoplasmic region ( Sirpa mut/mut ) and myeloid cell-specific Sirpa -knockout mice are protected from atherosclerosis. Further, global Cd47 −/− mice are protected from atherosclerosis but myeloid cell-specific deletion of Cd47 increased atherosclerosis development. Using a combination of techniques, we show that loss of SIRPα signalling in macrophages stimulates efferocytosis, reduces cholesterol accumulation, promotes lipid efflux, and attenuates oxidized LDL-induced inflammation in vitro and induces M2 macrophage phenotype and inhibits necrotic core formation in the arterial wall in vivo . Conversely, loss of myeloid cell CD47 inhibited efferocytosis, impaired cholesterol efflux, augmented cellular inflammation, stimulated M1 polarization, and failed to decrease necrotic core area in atherosclerotic vessels. Finally, comprehensive blood cell analysis demonstrated lower haemoglobin and erythrocyte levels in Cd47 −/− mice compared with wild-type and Sirpa mut/mut mice. Conclusion: Taken together, these findings identify SIRPα as a potential target in atherosclerosis and suggest the importance of cell-specific CD47 inhibition as a future therapeutic strategy. Graphical Abstract: